Dose-response relationship between external load and wellness in elite women`s soccer matches: Do customized velocity thresholds add value? - Scott, D.; Norris, D.; Lovell, R. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine the dose-response relationship between match-play high-speed running (HSR), very high-speed running (VHSR), and sprint (SPR) distances versus subsequent ratings of fatigue and soreness. Methods: Thirty-six outfield players competing in the professional National Women`s Soccer League (NWSL, United States) with a minimum of five 90-minute match observations were monitored during the 2016 and 2017 seasons (408 match observations, 11 [6]/player). HSR (=3.47 m·s-1), VHSR (=5.28 m·s-1), and SPR (=6.25 m·s-1) were determined generically (GEN) in players using a 10-Hz global positioning system. HSR, VHSR, and SPR speed thresholds were also reconfigured according to player peak speed per se and in combination with the final velocity achieved in the 30:15 Intermittent Fitness Test (locomotor approach to establishing individual speed zones). On the morning following matches (match day [MD + 1]), players recorded subjective wellness ratings of fatigue and soreness using 7-point Likert scales. Results: Fatigue (-2.32; 95% CI, -2.60 to -2.03 au; P < .0001) and soreness (-2.05; 95% CI, -2.29 to -1.81; P < .0001) ratings worsened on MD + 1. Standardized unit changes in HSRGEN (fatigue: -0.05; 95% CI, -0.11 to 0.02 and soreness: -0.02, 95% CI, -0.07 to 0.04) and VHSRGEN (fatigue: -0.06; 95% CI, -0.12 to 0.00 and soreness: -0.04; 95% CI, -0.10 to 0.02) had no influence on wellness ratings at MD + 1. Individualized speed thresholds did not improve the model fit. Conclusions: Subjective ratings of fatigue and wellness are not sensitive to substantial within-player changes in match physical performance. HSR, VHSR, and SPR thresholds customized for individual players` athletic qualities did not improve the dose-response relationship between external load and wellness ratings.